THE MEANING OF MEN'S DEGREES ARE HIGHER OVER WOMEN (Application of Roland Barthes Semiotics Against QS Al-Baqarah [2]:228) - Alfi Ifadatul Umami (Universitas Ahmad Dahlan, 2021)
This paper discusses the meaning of the word darajah in The Qur'an in particular in QS al-Baqarah [2]:228 which seems to be used as legitimacy for gender-biased people who think that women are left behind. In the study of semiotics, the word darajah is a symbol in the delivery of messages that must be interpreted. One of the relevant semiotic theories to be used in this paper is Roland Barthes' semiotics. In general, the semiotics offered by Barthes have two stages. The first stage is called the linguistic system and the second stage is called the mythological system. Next, the author will apply Barthes' semiotic theory to understand the meaning of the word darajah in QS al-Baqarah [2]: 228. The result is namely, the linguistic system in the word darajah is defined as position, leadership, and the rank of men is higher than women. While the mythological system is the meaning of the word darajah in this verse, namely the husbands have more right to take the wife back if he wants reconciliation with good intentions. The ideology or message contained in the verse is the relationship between husband and wife who have equal rights and obligations in the household.